1985
DOI: 10.1364/ol.10.000624
|View full text |Cite
|
Sign up to set email alerts
|

Generation of infrared supercontinuum covering 3–14 μm in dielectrics and semiconductors

Abstract: Infrared supercontinua spanning the range 3-14 microm were observed when an intense pulse generated from a CO(2) laser was passed into GaAs, AgBr, ZnSe, and CdS crystals. These supercontinua have been qualitatively compared with theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…The first observation of a SC dates back to 1970, when Alfano and Shapiro [3] focused powerful picosecond pulses into a glass sample and the observed continuum covered visible and near-infrared wavelengths. In the following years, similar broadening was observed in other solids, like semiconductors [4], also in H 2 O and D 2 O in 1977 [5] and in a jet stream of gaseous ethylene glygol in 1983 [6]. Nowadays, SCG has many novel applications in the field of telecommunication [7], highprecision frequency metrology [8], carrier phase stabilization [9], medical imaging [10] and pulse compression.…”
Section: Introductionmentioning
confidence: 57%
“…The first observation of a SC dates back to 1970, when Alfano and Shapiro [3] focused powerful picosecond pulses into a glass sample and the observed continuum covered visible and near-infrared wavelengths. In the following years, similar broadening was observed in other solids, like semiconductors [4], also in H 2 O and D 2 O in 1977 [5] and in a jet stream of gaseous ethylene glygol in 1983 [6]. Nowadays, SCG has many novel applications in the field of telecommunication [7], highprecision frequency metrology [8], carrier phase stabilization [9], medical imaging [10] and pulse compression.…”
Section: Introductionmentioning
confidence: 57%
“…The WLC can be generated by focusing high energetic short pulses into a transparent medium such as water [22], glass [31], optical fiber [32], photonic crystals [33], dielectric and semiconductors [34], crystals such as BaF 2 [35] and inert gases such Krypton or Ar [36,37]. We produced WLC by slightly focusing femtosecond pulses into a hollow fiber filled with Ar gas.…”
Section: Introductionmentioning
confidence: 99%
“…There have been, however, only a limited number of such reports in MIR. Corkum et al [2] observed spectral broadening of picosecond pulses of 600-PJ energy at 9.3-Pm wavelength in semiconductor materials. Kapetanakos et al [3] numerically studied the modulation instability inside GaAs with two closely-spaced radiation lines of a CO 2 laser.…”
Section: Introductionmentioning
confidence: 99%